2016
DOI: 10.1038/srep38427
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Association in Plants

Abstract: In complex and ever-changing environments, resources such as food are often scarce and unevenly distributed in space and time. Therefore, utilizing external cues to locate and remember high-quality sources allows more efficient foraging, thus increasing chances for survival. Associations between environmental cues and food are readily formed because of the tangible benefits they confer. While examples of the key role they play in shaping foraging behaviours are widespread in the animal world, the possibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
184
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 43 publications
2
184
0
1
Order By: Relevance
“…Some of these are resuscitated by signals such as blue light, known to involve ion flux (Trewavas, 2009). Associative, memory-based, forms of plant learning have recently been reported (Gagliano, 2017;Gagliano, Vyazovskiy, Borbely, Grimonprez, & Depczynski, 2016).…”
Section: Learning and Memory May Reside In Bioelectric Fieldsmentioning
confidence: 99%
“…Some of these are resuscitated by signals such as blue light, known to involve ion flux (Trewavas, 2009). Associative, memory-based, forms of plant learning have recently been reported (Gagliano, 2017;Gagliano, Vyazovskiy, Borbely, Grimonprez, & Depczynski, 2016).…”
Section: Learning and Memory May Reside In Bioelectric Fieldsmentioning
confidence: 99%
“…Plants have been omitted from the conversation because no experimental evidence for their ability to learn by association was available, until now 9 . It is logical then, that the adaptive value of associative learning in vegetal species has never been considered.…”
Section: The Ecology Of Associative Learning: a Case For Plantsmentioning
confidence: 99%
“…Over the last decade, there has been substantial debate in neurobiology and philosophy of mind regarding what kinds of organisms possess the capacity to learn (Gagliano et al , 2016(Gagliano et al , , 2018Thellier, 2017;Gagliano, 2017) , along with thornier issues like cognition (Garzón, 2007;Gross, 2016;Adams, 2018;Segundo-Ortin and Calvo, 2019) and intelligence (Marder, 2013;Trewavas, 2017) . Some of these disputes center around particular terminology and language, but some basic empirical questions remain contentious, including the simple question: can plants learn?…”
Section: Introductionmentioning
confidence: 99%
“…These studies generally failed to observe conditioning in plants, and those that concluded in favor of conditioning lacked sufficient controls to rule out other explanations, as reviewed by Adelman (Adelman, 2018) . Gagliano et al . (Gagliano et al , 2016) provide the most convincing report of conditioning in plants to date, but there are no published reports of replication, from the original lab or others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation